Assessing the impact of governance programmes: GIZ support to citizen participation in local governance in Benin - Lisa Groß (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
How can we assess impact in governance programmes? This publication provides an exemplary impact assessment of a decentralisation programme in Benin. It analyses whether and how external support to citizen participation contributes to the quality of public services and local governance in the context of Benins decentralisation process. The GIZ decentralisation programme has been supporting citizen participation since 2012, promoting different citizen participation formats at municipal level through low-level financial assistance, capacity building, accompaniment and advice to municipal authorities and civil society in selected partner municipalities. The study measures the effect of GIZ activities on the quality of selected citizen participation formats and evaluates the impact of these citizen participation formats on the quality of public service provision and local governance. Several recommendations can be drawn from the study for a successful promotion of citizen participation in decentralisation contexts: The promotion of citizen participation through a multi-stakeholder approach can increase the effectiveness of citizen participation. The example of Benin showed that support to citizen participation was more likely to yield improvements in local governance or public services where international actors had cooperated with both municipal authorities and civil society. A multi-level approach in the promotion of citizen participation can increase the sustainability of citizen participation in decentralisation. International actors in Benin lobbied at national level to include particular citizen participation mechanisms in the legal framework and the inclusion in the national-level framework helped to spread citizen participation practices nationwide. International actors need to make a long-term commitment in order to increase the sustainability of citizen participation. The example of Benin shows that those citizen participation mechanisms that were supported for more than five years were more likely to be sustained by partner municipalities, while practices with one-time support were less likely to be repeated. The intensity of international support also makes a difference with regard to the quality of citizen participation mechanisms. The more intensive the support to a citizen participation format, the higher the quality of implementation regarding the application of rules and regulations. To support citizen participation successfully, international actors should concentrate on a few mechanisms – following the motto ,,less is more“ - and refrain from experimenting with a high number of approaches at the same time in order to ensure clear communication to the partner municipalities. Focusing on a few approaches facilitates the goal of building sustainable institutions.
Keywords: 330; Wirksamkeit und Evaluierung; Governance